Avaliação da expressão de Rankl no tecido ósseo após a instalação de implantes em tíbia de coelho com diferentes torques de inserção - Rodrigues , André dos Santos (2014)
The present study aimed to evaluate the expression of RANKL protein after 40 days of insertion of osseointegrated implants with different insertion torques. Six healthy male adult New Zeland rabbits received two types of implants, Porous Nano and Porous, in the right tibia. The implants were installed with different torques. The animals were sacrificed on days 0 and 40. The implants were removed and the bone specimens were subjected to immunohistochemical analysis to quantify the expression of RANKL. Data were analyzed by Mann-Whitney test and Spearman correlation coefficient. The applied insertion torques on Porous and Porous Nano implants ranged from 20 to 40 N.cm, and the mean was 30 N.cm ± 8.16 for Group Day 0 for both implants; And, for Group Day 40, 25 N.cm ± 7.07 for both implants. There were no significant differences between groups neither between types of implants regarding insertion torque (p > 0.05). In the Group Day 40, the percent of stained cells for RANKL was 59.8% and, in the Group Day 0, 55.5%. Regarding proportions for Groups Day 0 and 40, the values were 1.66 and 1.50, respectively. However, none of those values were significantly different (p > 0.05). Analysis of correlation between insertion torque and percent of stain cells for RANKL in the bone tissue showed a significant negative correlation (rho = -0.926; p = 0.008) when both groups were considered. The expression of RANKL was similar between both experimental times. However, there was a significant negative correlation between insertion torque and the expression of RANKL in the bone tissue